Real-World Data from Turkey: Is Sofosbuvir/Ledipasvir With or Without Ribavirin Treatment for Chronic Hepatitis C Really Effective? - Demirtürk, Neşe; Aygen, Bilgehan; Çelik, İlhami and Mıstık, Reşit and Akhan, Sıla and Barut, Şener and Ural, Onur and Batırel, Ayşe and Şimşek, Funda and Ersöz, Gülden and et al. (Turkish Journal of Gastroenterology, 2021)
Background: In this study, we aimed to investigate the efficacy and safety of sofosbuvir-based therapies in the treatment of chronic hepatitis C in real-world clinical practice. Methods: Data from patients with chronic hepatitis C treated with SOF/LDV ± RBV or SOF/RBV in 31 centers across Turkey between April 1, 2017, and August 31, 2018, were recorded in a nationwide database among infectious disease specialists. Demographics, clinical, and virological outcomes were analyzed. Results: A total of 552 patients were included in the study. The mean age of the patients was 51.28 ± 14.2, and 293 (55.8%) were female. The majority had HCV genotype 1b infection (65%), 75.04% of the patients underwent treatment, and non-cirrhosis was present at baseline in 381 patients (72.6%). SOF/LDV ± RBV treatment was given to 477 patients and 48 patients received SOF/RBV according to HCV genotype. The total SVR12 rate was 99% in all patients. Five patients experienced disease relapse during the study and all of them were genotype 2. In patients infected with HCV GT2, SVR12 was 77.3%. SVR was 100% in all patients infected with other HCV genotypes. All treatments were well tolerated by patients without causing severe adverse events. Side effects and side effects-associated treatment discontinuation rates were 28.2% and 0.4%, respectively. Weakness (13.7%) was the common side effect. Conclusion: The present real-world data of 525 patients with HCV genotypes 1, 1a, 1b, 3, 4, and 5 who underwent SOF/LDV ± RBV treatment in Turkey demonstrated a high efficacy and safety profile. HCV GT2 patients should be treated with more efficacious treatment.